AMELIORATIVE ROLE OF SILYMARIN EXTRACTED FROM SILYBUM MARIANUM SEEDS ON NICKEL CHLORIDE INDUCE CHANGES IN TESTICULAR FUNCTIONS IN ADULT MALE RABBITS. - Abdul Razak N. Khudair; Eman A . AL-Masoudi; Wasfi Dh Abid Ali (Basrah Journal of Veterinary Research)
This study aimed to investigate the Ameliorative effect of ethanolic extracted of silymarin from Silybum marianum seeds and to compare it’s with the commercial silymarin extract(legalon) against oral dosing of Nickel chloride effects on sperms concentration, motility ,viability, sperm abnormality and male fertility and gonadal hormones .Twenty adult male rabbits aged 5 to 6 month and weighted 1.250-1.500 kg divided into four equal groups,1 st group served as control group received 1 ml of normal saline (NaCl 0.9%),2 nd group received (1mg/100g B.W )NiCl2 orally, 3 rd group received same dose of NiCl2 plus (0.1mg/100g B.W) silymarin extract, the fourth group received same dose of NiCl2 plus (0.1mg/100g B.W) legalon for 35 days, Results showed negative effects of NiCl2 which caused significant(p≤0.05) decrease in sperm concentration ,viability, motility and fertility while sperm abnormality was significantly increase, also NiCl2 caused significant (p≤0.05) decrease in serum progesterone, estradiol and testosterone. while silymarin extract and legalon adverse the negative effects of NiCl2 and causing ameliorative effects on all the studied parameters .